2015
DOI: 10.1590/1517-869220152106112307
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento Nutricional E Estado Antropométrico De Atletas Universitários

Abstract: RESUMOIntrodução: O estudo do consumo alimentar fornece informações específicas sobre a ingestão de energia e nutrientes, podendo estar associado com o conhecimento sobre nutrição e alimentação. Nesse contexto, a entrada dos estudantes na universidade envolve uma tendência de transição nutricional e mudanças negativas no nível de atividade física, resultando em alterações importantes na sua composição corporal. Objetivo: Analisar a relação entre perfil antropométrico e o conhecimento nutricional de atletas uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
1
0
1
Order By: Relevance
“…Despite the scarce number of studies with athletes, positive effects similar to those of the present study can be observed in other populations. In a study conducted by Rêgo et al 40 with postgraduate students in the health area, the methodology of the Maguerez Arch was considered adequate, stimulating, innovative and facilitating, making possible the interrelation between students and teachers, as well as between theory and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scarce number of studies with athletes, positive effects similar to those of the present study can be observed in other populations. In a study conducted by Rêgo et al 40 with postgraduate students in the health area, the methodology of the Maguerez Arch was considered adequate, stimulating, innovative and facilitating, making possible the interrelation between students and teachers, as well as between theory and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Percebe-se com este resultado que o conhecimento nutricional dos estudantes não foi acompanhado por um perfil nutricional eutrófico. Os estudos mostram pouca influência do nível de conhecimento nutricional sob a composição corporal dos indivíduos, pois as práticas alimentares são determinadas por aspectos de cunho cultural, educacional e econômico, sendo o conhecimento nutricional importante, mas não um fator isolado para mudar o Research, Society and Development, v. 10, n. 3, e33110313275, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i3.13275 comportamento alimentar (Dattilo et al, 2009;Loureiro, 2016;Montero Bravo et al, 2006;O'brien & Davies, 2007;Rêgo et al, 2015).…”
Section: Conhecimento Nutricionalunclassified
“…In Brazil, there is currently no validated questionnaire to assess the NK of Brazilians. Most studies have used adaptations of questionnaires from other populations or used non-validated instruments [ 9 , 10 , 11 , 12 , 13 ]. The lack of methodological rigor and absence of sport-related inquiries elevate the potential for bias in the obtained results.…”
Section: Introductionmentioning
confidence: 99%